2022
DOI: 10.1002/ajmg.a.62987
|View full text |Cite
|
Sign up to set email alerts
|

ERI1: A case report of an autosomal recessive syndrome associated with developmental delay and distal limb abnormalities

Abstract: ERI1 is an evolutionary conserved 3′–5′ exonuclease with an important function in multiple RNA processing pathways. Although the molecular mechanisms in which ERI1 is involved have been studied extensively in model organisms, the pathology associated with ERI1 variants in humans has remained elusive because no case has been reported so far. Here, we present a case of a female patient with a homozygous nonsense variant in ERI1 gene. The patient exhibits mild intellectual disability, eyelid ptosis, and anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…While ERI1 deletion likely plays a role in this pathology, it cannot solely be attributed to it (Choucair et al, 2017). Another patient was also identified recently as having a homozygous nonsense mutation (K188Stop) (Hoxha and Aliu, 2023). Similarly, this patient presented with limb abnormalities and intellectual disabilities, strengthening the case that ERI1 loss was the disease-causing mutation in the previous case.…”
Section: North American Indian Childhood Cirrhosismentioning
confidence: 71%
“…While ERI1 deletion likely plays a role in this pathology, it cannot solely be attributed to it (Choucair et al, 2017). Another patient was also identified recently as having a homozygous nonsense mutation (K188Stop) (Hoxha and Aliu, 2023). Similarly, this patient presented with limb abnormalities and intellectual disabilities, strengthening the case that ERI1 loss was the disease-causing mutation in the previous case.…”
Section: North American Indian Childhood Cirrhosismentioning
confidence: 71%
“… 47–49 The ERI1 gene might affect OSA and BMI through effects on growth and development, as well as cardiac functioning and disease. 50–52 A homozygous nonsense variant in ERI1 has been linked with developmental delay and distal limb abnormalities. 50 Choucair found that the homozygous microdeletion of ERI1 was correlated with the presence of intellectual disability, limb abnormalities, and cardiac malformation.…”
Section: Discussionmentioning
confidence: 99%
“… 50–52 A homozygous nonsense variant in ERI1 has been linked with developmental delay and distal limb abnormalities. 50 Choucair found that the homozygous microdeletion of ERI1 was correlated with the presence of intellectual disability, limb abnormalities, and cardiac malformation. 51 Chai et al discovered that SNPs in ERI1 were both associated with blood pressure and spontaneous coronary artery dissection.…”
Section: Discussionmentioning
confidence: 99%